GAMBARAN SELF EFFICACY SISWA TERHADAP PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Fickar Galaby; Nandang Rukanda; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The purpose of this study is to find out the description of students' self-efficacy towards online learning during the covid-19 pandemic. Students who have high self-efficacy will have a passion for learning and be able to survive when facing many school assignments. The phenomenon that occurs during learning during the COVID-19 pandemic, there are some students who experience low self-efficacy. This can be seen from the lack of enthusiasm in learning, easily stressed when many tasks and tend not to do school assignments that have been given. The method used in this study is a qualitative method with the type descriptive research. Data collection techniques used are interviews and documentation studies. The results obtained showed that three students of class XI had low self-efficacy towards learning during the COVID-19 pandemic.Keywords: Student, Self efficacy, Online learning, Covid-19